Follow-up Study of Mortality after Clinical Protocol Based Intervention at Emergency of Patan Hospital - Bajrachraya, Sumana; Shrestha, Ashis (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Decreasing the mortality of patients is one of the major concerns of emergency department. Mortality decreases after implementation of protocol based intervention. This follow up study has been done to see the benefit of protocol based approach. Methods: This was a cross sectional study conducted at emergency department of Patan hospital from January 2013 to June 2013. All records of patient with mortality were reviewed excluding those who were brought dead. Results: Total mortality in six months was 31. Mortality rate was 1.7 per thousand emergency visits. Mean duration of stay at emergency was five hours, range 30 minutes to 25 hours. The common diagnoses at presentation were Pneumonia 12 (45.1%), Upper gastrointestinal tract bleeding 4 (13%), Hypoglycaemia 3 (9.7%) followed by blunt abdominal trauma, penetrating neck injury, pneumothorax, spinal shock, head injury and zinc phosphide poisoning 2 (6.5%) each. The most common causes of death were septic shock 9 (29%), hypovolaemic shock 7 (25.8%), respiratory failure 6 (19.4%), hypoglycaemia 3 (9.7%), cardiogenic shock, raised intracranial pressure and spinal shock 2 (6.5%) each. Conclusions: Protocol based management are important tools to decrease mortality but it is not the only factor that decreases the mortality. Plain Language Summary: This study was done to see if implementing protocol based management improves mortality or not. This study highlighted the fact that protocol based management are important sufficient to decrease mortality. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13009   Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):13-15